Gerakan Tungku Api Kehidupan, Gerakan Bersama Menghadapi “Perubahan”. Berteologi Model Antropologis di Paroki Modio, Keuskupan Timika, Papua - Yeuyanan, Ricky Carol (Perspektif, 2019)
The focus of this article is searching the meaning of “perubahan” (development, change) and its impact to the life of the people in the parish of Modio, Diocese of Timika, Papua. Inspired by Bevans’ Models of Contextual Theology, the writer tries to explore the implementation of “Gerakan Tungku Api” (‘TungkuApi’ Movement) carried out in the parish. It is basically a pastoral evaluation, using literatures on the topic and particularly a participant observation. The article then offers some suggestions and recommendations, for the pastoral teams in particular, who are responsible for maintaining the unity in the society, promoting the understanding of (local) culture, and organizing collaboration among individuals and institutions